Serogroups and genetic diversity of diarrheagenic strains of Escherichia coli: a retrospective study - Mare, Anca; Man, Adrian; Ciurea, Cristina Nicoleta; Pintea-Simon, Ionela Anca; Ianoși, Edith Simona; Gîrbovan, Cristina Elena; Toma, Felicia (The Journal of Infection in Developing Countries, 2022)
Introduction: Diverse serogroups of Escherichia coli cause sporadic cases and outbreaks of diarrhea among children. Our study aimed to evaluate the serogroups of diarrheagenic strains of E. coli that cause diarrheal disease in children under two years old, and clarify if the cases were sporadic or outbreaks. Methodology: The retrospective study included 130 strains of pathogenic E. coli, isolated from children who were less than two years of age, and had diarrheal disease, between May 2016 and July 2019. The study was conducted in the Bacteriology Laboratory (County Clinical Hospital, Mureș, Romania). The 130 strains were sero-grouped using polyvalent and monovalent O antisera. Enterobacterial Repetitive Intergenic Consensus-PCR (ERIC-PCR) was performed to evaluate the similarity between different E. coli strains, and a simplex polymerase chain reaction (PCR) was performed to detect the presence of the hlyA gene that is specific to the enterohemorrhagic strains. Results: After agglutination with polyvalent O antisera, slightly more than half of the strains (50.77%) were sero-grouped as Shiga toxin-producing E. coli (STEC), and the rest of the strains belonged to the Enteropathogenic Escherichia coli (EPEC) serogroups. Serogroup O157 was the most frequently identified (16.51% of the total number of typeable strains), and one strain was positive for hlyA. ERIC-PCR revealed a high diversity of strains, with an overall 50% similarity. Conclusions: STEC serogroups were the most common strains causing diarrheal disease, and O-157 was the dominant serogroup identified. The strains included in our study presented high genetic diversity, suggesting that most of the cases were sporadic.